Design and implementation of data compressor and decompressor with advanced data compression algorithm - Oey, Richard (2012)
The objective is to research for best data compression algorithm and to implement the compressor in software and decompressor in hardware to effectively decrease the size of a software code stored in a memory. The overall hardware size of the data decompressor and memory could be greatly reduced. This project, student will need practice knowledge in data compression algorithm, software design and hardware design(from rtl to synthesis), as well as verification of the design and technique in justisfy the results with proof of area,logic and efficiency.